1996
DOI: 10.3928/0098-9134-19960101-07
|View full text |Cite
|
Sign up to set email alerts
|

TRAINING STAFF TO PREVENT AGGRESSIVE BEHAVIOR of Cognitively Impaired Elderly Patients During Bathing and Grooming

Abstract: 1. Cognitively impaired elderly patients often become aggressive toward caregivers who are providing assistance with bathing and grooming, but caregivers can learn methods to prevent or reduce some of the aggression. 2. The R.E.S.P.E.C.T. model describes key practices caregivers can use to better meet patient needs and reduce aggression, increasing their understanding and skill. 3. In addition to training, observation of performance and consultation are important steps in enabling caregivers to apply and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
2
32
0
1
Order By: Relevance
“…This is not surprising and a common finding in the literature (Cohn, Horgas, & Marsiske, 1990;McCallion, Toseland, Lacey et al, 1999). In most studies, including follow-ups, no long-term effects could be confirmed (Campbell, Knight, Benson et al, 1991;Maxfield, Lewis, & Cannon, 1996). Therefore our results are encouraging and support the concept and materials used in our approach.…”
Section: Discussionsupporting
confidence: 85%
“…This is not surprising and a common finding in the literature (Cohn, Horgas, & Marsiske, 1990;McCallion, Toseland, Lacey et al, 1999). In most studies, including follow-ups, no long-term effects could be confirmed (Campbell, Knight, Benson et al, 1991;Maxfield, Lewis, & Cannon, 1996). Therefore our results are encouraging and support the concept and materials used in our approach.…”
Section: Discussionsupporting
confidence: 85%
“…However, by 12-week follow-up, this effect was no longer evident. Maxfield et al (1996) problems exhibited by patients, as well as improvement in staff performance.…”
Section: Magai Et Al (2002)mentioning
confidence: 95%
“…However, this program suffers from the methodological problems reported in other studies: a small sample size, no control group, and self reports by trainees on the nature of the skills that they have developed. Similar to the program designed by Hagen and Sayers (1995), Maxfield, Lewis and Cannon (1996) developed a program that trained staff to prevent aggressive behavior among elderly patients with dementia. The results demonstrated that the knowledge and skill base of staff increased after training.…”
Section: Studies That Do Not Include a Control Groupmentioning
confidence: 99%
“…In a state-operated geropsychiatric hospital, Max®eld et al (1996) examined the eects of training licensed and unlicensed nursing sta to prevent aggressive behavior of patients with dementia during bathing and grooming. They used a pre-/post-test research design.…”
Section: Studies Evaluating Training Programsmentioning
confidence: 99%